The Literature Review on the Effectiveness of Fall-related Hip Fracture Prevention Programs - Se-young Lee; Seung-su Kim; Kitaek Lim; Woochol Joseph Choi (Korean Research Society of Physical Therapy, 2021)
While efforts have been made to address fall-related injuries in older adults, the problem is unsolved to date. The purpose of this review is to provide a guideline for fall and injury prevention programs in older adults, based on evidence generated over the past 30 years. Research articles published between 1990 and 2020 have been searched on PubMed, using keywords, including but not limited to, falls, hip fracture, injuries, intervention, older adults, prevention, hip protector, vitamin D, safe landing strategy, and exercise. Total of 98 articles have been found and categorized into five intervention areas: exercise program, hip protector, safe landing strategy, vitamin D intake, and compliant flooring. Furthermore, the articles have been rated based on their study design: class 1, randomized controlled trials; class 2, nonrandomized controlled trials; class 3, experimental studies; class 4, all other studies. Exercise programs have shown to decrease the risk of fall, and associated injuries. Hip protectors, safe landing strategy, and vitamin D intake were effective in reducing a risk and incidence of hip fracture during a fall. Furthermore, compliant flooring has also decreased hip fracture risk without affecting balance. An integrated approach combining exercise program, wearing a hip protector, teaching safe landing strategies, scheduled vitamin D intake, and compliant flooring installation, is suggested to address fall-related injuries in older adults.